Agronomic Performance Of S1 Maize Lines Derived From A Bi-Parental Cross Under Infested And Striga Free Environments - Abdoul-Madjidou Yacoubou; Nouhoun Zoumarou Wallis; Hafiz Adio Salami; Alain S. Yaoitcha; Abebe Menkir; Ojo Tayo; Paterne Angelo Agre (European Scientific Journal, ESJ, 2021)
Striga hermonthica, causes up to 100% yield loss in maize production in sub-Saharan Africa. Developing Striga resistant maize cultivars could be a major component of integrated Striga management strategies. This study aims at assessing the agronomic performance of S1 breeding lines in improving maize for Striga resistance. Two hundred S1 lines have been evaluated under artificial infestation Striga and Striga-free conditions in Benin for two years during 2018 and 2019 growing seasons using alpha-lattice design (51 x 4) with two replicates. Twelve agro-morphological and Striga adaptive traits have been assessed. The tested lines have displayed high genetic variability for most agronomic and Striga adaptive traits. The S1 lines exhibited high grain yield than their parents with averages of 2,552.72±593 kg ha-1 and 2,965.67±635.86 kg ha-1 under Striga artificial infestation and Striga-free conditions, respectively. Grain yield has displayed high positive and significant genetic and phenotypic correlations with ears per plant and high negative correlations with days to 50% silking, ears aspect, and Striga damage rating at 8 and 10 weeks after planting (WAP). Useful traits like ears per plant, days to 50% silking, ears aspect, number of emerged Striga plants and Striga rating at 10 WAP could assist for indirect selection under Striga conditions. Based on the selection index, a total of 15 S1 lines have been identified as top ranking and can be used as sources of resistance or tolerance genes to Striga and further improvement in maize breeding in future.